Patent as a motivation of starting a new entrepreneurial activity of high potential - Iraklis Goniadis; Yannis Goniadis (International Journal of Economic Sciences and Applied Research, 2010)
This paper entitled Patent as a motivation of starting a new entrepreneurial activity of high potential based on a research that was held by the Greek Industrial Property Organization (O.B.I.), investigates the fate of Patents that the organization granted to residents of the country during the period 1995-2005. Attempts to reveal the ways of exploitation of the patents by the inventors and tries to answer the question whether the patent can be a strong motive for the patentee to start a new venture. The main results summarized as follows: 1) a significant number of patentees started a new business with most of them being optimistic of new job creation, 2) a smaller number of patentees transferred or sold their patent rights to third persons directly contributing to the technological upgrade of established enterprises or, indirectly, to the advancement of entrepreneurship in Greece, 3) the biggest proportion of the patent holders remained inactive, without any exploitation of their patent, alleging several reasons for that.
Keywords: L26; O31; O34; 330; entrepreneurship; patent rights; and innovation